A COMPREHENSIVE REVIEW ON NOVEL MICROSPONGES DRUG DELIVERY APPROACH - Kumari, Pushpa; Mishra, Shashi Kiran (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Microsponges drug delivery approach (MDA) has been introduced in topical products to facilitate the controlled and targeted release of active drug into the skin to decrease systemic exposure and minimize local cutaneous reaction. Microsponges are highly cross-linked, polymeric sponge, porous in nature, spherical shape consisting of high drug content within their interconnecting voids, releasing bioactive agent at a target site within predetermined time. They are mostly used for prolonged topical administration, enhanced efficacy for topically therapeutic agent with safety, stability and reduced side effects followed by improved aesthetic properties in an efficient and novel manner. More ever, it is found to be stable over wide pH range and compatible with most vehicles. We here complied recent data regarding properties of microsponges, their methodology pharmaceutical application and list of patent till date. Keywords: Microsponges, Bioactive, Porous, Interconnecting voids, Aesthetic.